Minimizing the total completion time in a two-machine flowshop problem with time delays. Issue 7 (2nd July 2016) - Msakni, Mohamed Kais; Khallouli, Wael; Al-Salem, Mohamed; Ladhari, Talel
Abstract : This article proposes to solve the problem of minimizing the total completion time in a two-machine permutation flowshop environment in which time delays between the machines are considered. For this purpose, an enumeration algorithm based on the branch-and-bound framework is developed, which includes new lower and upper bounds as well as dominance rules. The computational study shows that problems with up to 40 jobs can be solved in a reasonable amount of time.